IMPLEMENTASI PENGEMBANGAN KURIKULUM MERDEKA DI SDN WALAHAR I KARAWANG - Nina Erma Januarsih; Kurnia Meida Dewi; Nula Tutilawati; Riska Dwi Hamidah; Nur Aini Farida (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2023)
This study aims to examine the implementation of kurikulum merdeka development at SDN Walahar 1 which includes: Teacher readiness in implementing an independent curriculum, school support in implementing an independent curriculum, supporting and inhibiting factors for implementing an independent curriculum, and steps to overcome obstacles to implementing an independent curriculum. This study uses a qualitative method with a descriptive approach. Data collection techniques used are interviews, observation, and documentation with data analysis methods, data presentation, and conclusion The process of implementing the independent curriculum has been carried out in grades 1 and grade 4 at SDN Walahar 1 with the option of changing the curriculum. By Following with per under the facts, the school only implements some parts of the independent curriculum and all teachers have not received training, including not implementing learning according to the Achievements of the Independent Curriculum and support from schools that are lacking in implementing the independent curriculum at SDN Walahar 1